Diagnostic imaging in paraneoplastic autoimmune multiorgan syndrome: retrospective single site study and literature review of 225 patients. (29th July 2014) - Lehman, Vance T.; Barrick, Benjamin J.; Pittelkow, Mark R.; Peller, Patrick J.; Camilleri, Michael J.; Lehman, Julia S.
Abstract: Background: The utility of diagnostic imaging in paraneoplastic autoimmune multiorgan syndrome (PAMS) is unknown. Methods: We examined the role of diagnostic imaging in patients with PAMS evaluated at our tertiary referral center (at Mayo Clinic, Rochester, MN, USA) and in the English literature between January 1, 1996, and August 31, 2012. Results: We included 17 patients from our institution and 208 patients from the literature review. Of these 225 patients, 113 (50.2%) were not known to have a malignancy diagnosis at the time of PAMS diagnosis. Of the 123 patients from our institution and from the literature reported to undergo imaging studies, conventional computed tomography (CT) was the predominant imaging modality ( n = 110; 89.4%); 18F‐fluorodeoxyglucose (18F‐FDG) positron emission tomography (PET)/CT was also used, albeit infrequently ( n = 12; 9.8%). When CT was included in imaging to identify or confirm the presence of a malignancy, imaging was successful in all patients who ultimately were diagnosed with an associated malignancy. At our institution, a relatively high percentage ( n = 7; 41%) of patients had 18F‐FDG PET/CT, which not only identified all tumors found on CT but also facilitated staging of lymphoma and guided biopsy procedures. Conclusion: Diagnostic imaging is frequently utilized in PAMS with unknown malignancy. Both conventional CT and 18F‐FDG PET/CT are likely to detect the typical underlying neoplasms. Relative to conventional CT, 18F‐FDG PET/CT may provide additional useful information regarding prognosis for the likely underlying malignancies, although there is a paucity of reports describing the use of this modality for this purpose.